The Financial Services Authority’s Market Conduct Supervision and Consumer Protection within Non-Bank - Muhammad Joddy AT Hasan; Muhamad Taufik La Ode (Journal of Legal Contemplation, 2026)
This research aims to analyze the regulatory and supervisory role of the Financial Services Authority (OJK) concerning consumer protection in the Non-Bank Financial Institution (NBFI) sector. The rapid growth of NBFIs carries complex legal risks, particularly regarding unethical collection practices and the use of unbalanced standard agreements. Using a normative legal research method with statutory and conceptual approaches, this study examines the legal certainty and normative implications of the implementation of Law Number 21 of 2011 and OJK Regulation (POJK) Number 22 of 2023. The main findings indicate an operational ambiguity regarding the definition of consumer "bad faith" in Articles 6 and 99 of POJK No. 22 of 2023, which remains multi-interpretable despite the provided explanations. This vague norm creates legal uncertainty and provides excessive discretion to business actors, thereby weakening the consumer's bargaining position in financial service disputes. The results conclude that strengthening consumer protection requires the formulation of concrete behavioral indicators within the regulatory framework to close the gap of subjectivity for both regulators and business actors.